2021
DOI: 10.21203/rs.3.rs-516417/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nano-curcumin Capped Au/ZnO Nanocomposite: A Promising Approach to Protect from Staphylococcus Aureus Infection through Inhibits Production of α-Hemolysin

Abstract: Gold with Zinc Oxide nanoparticles (Au@ZnO NPs) were prepared by laser ablation then capped with Curcumin nanoparticles. The ability of Nano-curcumin-Au/ZnO nanocomposite as a promising antibacterial agent was tested against Staphylococcus aureus. Cur-Au@ZnO NPs were characterized by TEM, FTIR spectroscopy, and Uv-spectroum. TEM image of Au@ZnO NPs has grain size almost 27–38 nm and it increased after capped Nano-curcumin to 72–113 nm. Agar well diffusion method was used to evaluate the antibacterial activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…These results are consistent with the current study findings. A preprint has previously been published (DOI: https://doi.org/10.21203/rs.3.rs-516417/v1 ), and it revealed that Cur-Au@ZnO NPs protect from bacterial infection through inhibiting production of α -hemolysin [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with the current study findings. A preprint has previously been published (DOI: https://doi.org/10.21203/rs.3.rs-516417/v1 ), and it revealed that Cur-Au@ZnO NPs protect from bacterial infection through inhibiting production of α -hemolysin [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…ROS can damage iron-sulfur enzyme cofactors. NP size, concentration, and stability in the growth medium affect bactericidal activity 58,59 .…”
Section: Contact Anglementioning
confidence: 99%